Skeletal indicators of developmental changes in arboreality and locomotor maturation in extant apes and their relevance to hominin paleobiology - Saers, Jaap P. P. (Frontiers in Ecology and Evolution, 2023)
Modern humans are the only fully terrestrial ape. All other apes are partially arboreal, particularly as infants and juveniles. Precocial locomotor development, high frequency of arboreal locomotion in early ontogeny, and increased terrestriality throughout development are ubiquitous amongst the non-human apes and likely represent the ancestral state for the African great apes. The role of climbing in hominin evolution has been debated for decades, but if hominins climbed regularly then subadults likely relied on it most frequently. Investigating the role of climbing throughout hominin evolution requires reliable developmentally plastic traits that are responsive to locomotor loading and can be identified in the fossil record. The aim of this paper is to validate whether age related variation in trabecular, cortical, and total bone volume fraction (BV/TV) may be used to reconstruct variation in locomotor behaviour during development. Chimpanzees and gorillas provide a natural experiment to examine the relationship between age-related variation locomotor activities and bone structure. Chimpanzees and gorillas are most arboreal during infancy and become more terrestrial throughout development. Gorillas are more terrestrial than chimpanzees and transition to predominantly terrestrial locomotion at an earlier age. This paper has two main objectives. First, to examine if variation in the rate of locomotor development is reflected in bone structure. Second, to determine if ontogenetic reductions in the frequency of arboreal locomotion correspond to age-related variation in bone structure. Results demonstrate that bone volume fraction (BV/TV) scales with positive allometry throughout ontogeny. The achievement of adult-like locomotor behaviour can be identified by a significant change in the slope of Total.BV/TV with age. Younger, more arboreal individuals have relatively greater upper limb Total.BV/TV relative to the neck and lower limb than older, more terrestrial individuals in gorillas and chimpanzees. More arboreal chimpanzees have relatively more Total.BV/TV in the upper limb relative to the lower limb and neck. The correspondence between developmental trajectories of bone structure and locomotor ontogeny in extant apes suggests that analyses of hominin skeletal ontogeny can provide new insights into the evolution of two characteristic human traits: our slow rate of maturation and the evolution of fully terrestrial bipedalism.